Implementation of Counseling Services for Students in Pandemi Time - Muhammad Putra Dinata Saragih; Devi Indah Sari (Britain International for Academic Research (BIAR) Publisher, 2022)
This study aims to analyse the Implementation of Counseling Services for Students in Pandemi Time. This study uses a type of qualitative research method. Bogdan and Taylor define qualitative methods as research procedures that produce descriptive data in the form of written words orally from people and observable behavior. Kirk and Miller define that qualitative research is a particular tradition in social science that is fundamentally dependent on human observation both in its field and in terminology. The conclusion that the researchers got from this mini-research or observation is that in providing guidance and counseling services, not all counseling teachers provided this service to students during a pandemic, and some did not even provide the service, if any, the service provided by the guidance teacher. Counseling to service students is only in the form of a warning if the student's hair is long, a warning for being late or not paying tuition fees, a warning regarding students who rarely attend school, informing students who have received scholarships, and also guidance if there is a competition. That's all the services provided.